Sense of coherence and intentions to retire early among Finnish women and men - Lahelma Eero; Koskenvuo Karoliina; Suominen Sakari; Volanen Salla-Maarit; Koskenvuo Markku; Silventoinen Karri (BMC, 2010)
Abstract Background Previous studies have shown that age, physical and mental health status and working circumstances, along with different socio-economic and psychosocial factors affect the retirement process. However, the role of psychological resources, such as sense of coherence (SOC), on the retirement process is still poorly understood. This study investigated the associations between SOC and intentions to retire early and whether these associations were explained by socio-economic, psychosocial and work and health related factors. Methods The data were derived from the Finnish Health and Social Support (HeSSup) Study. The information was gathered from postal surveys in 1998 (baseline) and in 2003 (follow-up). The analyzed data consisted of 7409 women and 4866 men aged 30-54 at baseline. SOC and background factors including childhood circumstances, language, education, working circumstances, social support, health behaviour and somatic and mental health status were assessed at baseline. The intentions to retire early were assessed at follow-up using logistic regression analysis. Results SOC was associated with intentions to retire early among both genders. Socio-economic, psychosocial and work and health behaviour related factors did not influence the association between SOC and intentions to retire early among women and men reporting somatic or mental illness. Further, the association between SOC and intentions to retire early remained among (somatically and mentally) healthy men. Among healthy women the association was weaker and statistically non-significant. Among unhealthy women, the odds ratios of SOC was 0.97 (CI 95% 0.96-0.98) and 0.97 among ill men (CI 95% 0.96-0.98), i.e., each additional SOC score reduced the risk of intentions by 3% among both genders. Conclusion Unhealthy employees with low SOC and low education were in the greatest risk to have reported intentions to retire early. SOC had an independent effect on intentions to retire early, and a strong SOC may have a potential to prevent early retirement in groups otherwise at risk. An important challenge would be to target the resources of SOC to the most vulnerable and design appropriate interventions in order to strengthen the level of SOC and hence prolong working years of the aging employees.